Nanocarrier system: state-of-the-art in oral delivery of astaxanthin - Abdol Wahab, Nur Rafiqah; Meor Mohd Affandi, Meor Mohd Redzuan; Fakurazi, Sharida; Alias, Ekram; Hassan, Haniza (MDPI AG, 2022)
Astaxanthin (3,3′-dihydroxy-4,4′-diketo-β-β carotene), which belongs to the xanthophyll class, has shown potential biological activity in in vitro and in vivo models including as a potent antioxidant, anti-lipid peroxidation and cardiovascular disease prevention agent. It is mainly extracted from an alga, Haematococcus pluvialis. As a highly lipid-soluble carotenoid, astaxanthin has been shown to have poor oral bioavailability, which limits its clinical applications. Recently, there have been several suggestions and the development of various types of nano-formulation, loaded with astaxanthin to enhance their bioavailability. The employment of nanoemulsions, liposomes, solid lipid nanoparticles, chitosan-based and PLGA-based nanoparticles as delivery vehicles of astaxanthin for nutritional supplementation purposes has proven a higher oral bioavailability of astaxanthin. In this review, we highlight the pharmacological properties, pharmacokinetics profiles and current developments of the nano-formulations of astaxanthin for its oral delivery that are believed to be beneficial for future applications. The limitations and future recommendations are also discussed in this review.